USING INQUIRY METHOD TO IMPROVE THE STUDENTS’ READING COMPREHENSION (A Classroom Action Research) - Wildhan Burhanuddin (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2012)
This research aimed to explain the improvement of the students’ reading comprehension in terms of literal comprehension dealing with and word meaning main ideas and interpretive comprehension dealing conclusion. To explain the improvement, the researcher used a classroom action research (CAR) which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken from the first semester students of English Education Department with a number of the subject were 25 students. The research findings indicated that the application of Inquiry Method was significant in improving the students’ reading comprehension in terms of literal comprehension and interpretive comprehension. It was proved by the mean score of the cycle I was 68, 47. It was classified as fair then improved to be 81, 20. It was classified as good in cycle II. They are higher than the mean score of diagnostic test namely 58.40 that classified as poor. Therefore there was the improvement of the students’ reading comprehension in terms of literal comprehension dealing with word meaning and main ideas and interpretive comprehension dealing conclusion.Keywords: Inquiry, Reading, Comprehension, Method.